Anaerobic filter treatment of wine distillery waste - Capri, Mario Giulio (Department of Civil Engineering, 2024)
In the Western Cape, the high strength wine distillery wastes (approximate COD of 24 000 mg/l) are stabilized by the anaerobic contact process. This process requires fairly close operational control, and a degree of technical competence which is often tacking in many small plants. McCarty has recently developed the submerged anaerobic fitter as an effective means for treating tow strength wastes. As the fitter was found to require little supervision to ensure efficient and stable operation, it was decided to enquire into the suitability of the fitter for the treatment of wine distillery waste. The specific objectives of the investigation were to: 1. Compare the performance and behaviour of the anaerobic fitter with those of the contact process. 2. Investigate the effect of different fitter media on the process performance. 3, Apply the general kinetic model for biological systems to the anaerobic fitter process.